Targeted therapies in CLL/SLL and the cumulative incidence of infection: A systematic review and meta-analysis - Vassilopoulos, Stephanos; Shehadeh, Fadi; Kalligeros, Markos; Tran, Quynh-Lam; Schiffman, Fred; Mylonakis, Eleftherios (Frontiers in Pharmacology, 2022)
Background: Patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) are prone to infections. Aims: Provide a pooled estimate of the cumulative incidence for infections that fulfilled the criteria associated with severe infectious adverse events for grade 3 or higher (including pneumonia, febrile neutropenia and sepsis) in patients who receive targeted therapies. Methods: We searched PubMed and EMBASE for randomized controlled trials (RCT) that included patients with CLL/SLL who received targeted therapies and performed a random-effects meta-analysis to estimate the cumulative incidence of infections. Results: Of 2,914 studies screened, we retrieved 31 which evaluated 11,660 patients. The pooled cumulative incidence of infections for patients who received treatment regimens based on a BTK inhibitors was 19.86%. For patients who received treatment based on rituximab and 2nd generation anti-CD20 monoclonal antibodies, the pooled cumulative incidence of infections was 19.85% and 13.46%, respectively. Regarding PI3K inhibitor-based regimens the cumulative incidence of severe infections was 30.89%. BCL-2 inhibitors had a cumulative incidence of infections of 17.49% while lenalidomide and alemtuzumab had an incidence of 13.33% and 45.09%, respectively. The cumulative incidence of pneumonia ranged from 3.01 to 8.45% while febrile neutropenia ranged from 2.68 to 10.80%. Regarding sepsis, the cumulative incidence ranged from 0.9 to 4.48%. Conclusions: Patients with CLL/SLL who receive targeted therapies may develop severe infections at significant rates that, in addition to disease stage and other complications, depend on the mechanism of action of the used drug. Surveillance for infections and development of effective prophylactic strategies are critical for patients with CLL/SLL who receive targeted therapies.